A dietary dairy/yeast prebiotic and flaxseed oil enhance growth, hematological and immunological parameters in channel catfish at a suboptimal temperature (15°C). (6th March 2015) - Thompson, M.; Lochmann, R.; Phillips, H.; Sink, T. D.
<x content-type="archive" xml:space="preserve">Abstract</x> Channel catfish raised in the southern United States require two growing seasons to reach market size. Growing seasons are separated by a cool period of about 3 months when feed intake and growth are greatly reduced. A cool-weather feeding strategy to improve feed intake, growth or health of catfish might improve survival and reduce the time needed to achieve market size. We conducted a feeding trial with channel catfish at a suboptimal temperature (15°C) to determine the effects of supplementing diets with either a dairy/yeast prebiotic or flaxseed oil (high in 18:3n-3) compared with a control with soybean oil (high in 18:2n-6). The trial was conducted in recirculating systems with 1140-l tanks containing 100 fish each (mean initial weight 61.4 g±0.43 s.e.m.). A 28%-protein basal diet was supplemented with 20 g/kg cellulose and 20 g/kg soybean oil (SBO, control), 20 g/kg cellulose and 20 g/kg flaxseed oil (FLAX) or 20 g/kg of a dairy/yeast prebiotic and 20 g/kg soybean oil (PREB). Fish were fed once daily to satiation and weighed every 3 weeks to track growth. Hematology, non-specific immune responses, proximate and fatty acid composition of muscle were determined to assess diet effects. Catfish-fed FLAX or PREB had higher weight gain, feed consumption and lysozyme activity than fish fed SBO. Total n-3 fatty acids in muscle were higher in fish fed SBO or FLAX than those fed PREB. Total n-6 long-chain polyunsaturated acids were higher in muscle of fish fed PREB than those fed SBO. Fatty acids in the PREB and SBO diets were similar, so the PREB appeared to increase elongation and desaturation of n-6 fatty acids in muscle. Flaxseed oil and the dairy/yeast prebiotic both have potential to increase catfish performance at a low temperature.